If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 163 + -35x Solving 13 = 163 + -35x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '35x' to each side of the equation. 13 + 35x = 163 + -35x + 35x Combine like terms: -35x + 35x = 0 13 + 35x = 163 + 0 13 + 35x = 163 Add '-13' to each side of the equation. 13 + -13 + 35x = 163 + -13 Combine like terms: 13 + -13 = 0 0 + 35x = 163 + -13 35x = 163 + -13 Combine like terms: 163 + -13 = 150 35x = 150 Divide each side by '35'. x = 4.285714286 Simplifying x = 4.285714286
| 3-2=5 | | x+1-2-x-(-3)= | | 60xk-30=270 | | -57=2x+23 | | 3x^2-13x-9=0 | | x+1-2-x-(-2)= | | 7=-77-6x | | 7680-30= | | 120-4x=14x+24 | | 4x-2=2x+12 | | 132=4x+20 | | 13-9x=61-23x | | x=9.3333+1.33333y | | 2x-2=20x+6 | | -20=10-3x | | Z^4=-8-(-6) | | 3x+22=7x+26 | | 22-6x=18 | | 357x-35=5783x+5 | | 89=3x+23 | | -5x(4x-6)+5=-20x+35 | | x-4=5x-12 | | -8y-2=7y-3 | | 9w-7=3w+23 | | 5x+v=w | | 8x-10=5x+20 | | .333(4x+1)=3(1-3x)+18 | | 4x+11=2x+21 | | 4b^2-39b+77=0 | | 10(x-4)=70 | | 4a+6=20 | | 1/4.1.2= |